Vaccination Coverage Under the Expanded Program on Immunization in South West Cameroon - Bestina Forkwa Ewang, MSc; Mathias Esum Eyong, PhD; Samuel Nambile Cumber, PhD; Claude Ngwayu Nkfusai, MSc; Brenda Mbouamba Yankam, MSc; Cho Sabastine Anye, MSc; Jacintha Rebang Achu, MSc; Bih Moki Suh, MSc; Mildred Njoache Nkeng, MSc; Rosette Boseme Nzoyom, BSc; Joyce Mahlako Tsoka-Gwegweni, PhD; Eric Achidi Akum, PhD (Global Health and Education Projects, Inc., 2020)
Background: Inadequate vaccination coverage with increased risk of vaccine preventable disease outbreaks remain a problem in Africa. The aim of this study was to assess the vaccination coverage levels under the Expanded Program on Immunization (EPI) in a health area and to identify factors that affect vaccination coverage in view of providing valuable data for disease prevention. Methods: A cross-sectional household survey was conducted in August 2017 in the Mbonge health area, Southwest Cameroon. Clustered sampling technique was used to select study communities and a purposive sampling design was used to select households. An interviewer-administered questionnaire was used to obtain information from consenting caregivers of children aged 9-23 months. Vaccination coverage was assessed by consulting the vaccination cards and parents' recall. In households with more than one child aged 9-23months, the youngest was chosen. Results: Overall, 300 caregivers were enrolled into the study. The average vaccination coverage for the past three years (2014-2016) was 34.0%. Two hundred and fifty-five (85%) children had vaccination cards. Amongst the children, 143 (47.7%) had taken all vaccines as recommended while 30 (10%) had not received a single dose. Factors significantly associated with incomplete vaccination status included: occupation (being a farmer) (p-value=0.011), marital status (married) (p-value=0.048), caregiver's utilization of health facility (p-value=0.003), low levels of mothers' utilization of antenatal care (ANC) services (p-value=0.000), and low knowledge on vaccination (p-value=0.000). Conclusion and Global Health Implications: Adequate vaccination coverage can be attained through good sensitization and health education for primary caregivers. Targeting families living far away from vaccination centers, using appropriate communication and vaccination strategies may improve vaccination coverage in the Mbonge Health Area of South West Region, Cameroon. Key words: • Assessment • Vaccination Coverage Expanded Program on Immunization • Mbonge Health Area • Cameroon • EPI   Copyright © 2020 Ewang et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.